Promosi jasa berbasis daring oleh elsphotography sub melalui instagram - Charistia, Abigail Yuri; Yenny, Yenny (Soetomo Communication and Humanities, 2020)
Interactive media allows a reciprocal flow of information that allows users to participate and modify the contents of the information at that moment (Real time). This interactive ability is also owned by social networks like Facebook, Instagram and other social networks, this is what makes online media superior. Instagram is so quick to adapt to the development of this popular technology that is an added value for Instagram that is complete with chat features and active user status to be a facility that can turn on this social networking site. Instagram is also accessed via mobile or tablet, therefore Instagram is utilized as a very effective and very efficient marketing communication medium. Elsphotographysub is one of the photo shooters who use Instagram as a marketing communication service. Various strategies have been carried out to maintain the existence of competition in the photography industry which is currently in view of the market which is very potential in an effort to promote services widely. Although not too large, but Elsphotographysub has been well known by this audience as evidenced by the achievement of 1,311 Instagram users who have followed the Elsphotographysub diagram as of January 23, 2020 and for some people who have used Elsphotographysub services.Keywords: elsphotographysub; instagram; services; marketing.